Graphite negative electrode material and preparation method and application thereof
By adjusting the volume median particle size, specific surface area and side reaction signals of graphite negative electrode material to meet a specific range, the problem of difficult to take into account both the fast charging capability and circulation performance of lithium-ion batteries is achieved, and high magnification and long circulation performance are achieved. Take into account both.
Patent Information
- Application Number
- CN202411591167.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-18
AI Technical Summary
The fast charging capability and circulation performance of lithium-ion batteries are difficult to take into account at the same time, mainly because of the limitations of graphite negative electrode materials.
By adjusting the volume median particle size Dv50, specific surface area B and side reaction signal S of the graphite negative electrode material, it satisfies 8≤B×Dv50×S≤24, thereby having high magnification and long cycle performance.
The lithium-ion battery has achieved a low polarization degree in the process of large-scale lithium embedded in lithium, and the lithium-ion reaction is later, with excellent fast charging performance, and maintaining an initial capacity of 80% under high cycle times.
Smart Images

Figure BDA0005125624320000151
Abstract
Description
Technical Field
[0001] The invention belongs to the field of batteries, and in particular relates to a graphite negative electrode material and a preparation method and application thereof. Background Art
[0002] At present, lithium-ion batteries have become the mainstream battery for storing and using electrical energy. Among the many application scenarios of lithium-ion batteries, electric vehicles are the main source of demand for rechargeable lithium-ion batteries. When a lithium-ion battery is charged, under the action of an external voltage, lithium ions are released from the positive electrode material, enter the electrolyte, pass through the diaphragm, move to the negative electrode with the electrolyte, and finally embed into the negative electrode material. Studies have found that the main factor limiting the fast charging capability of lithium-ion batteries is the negative electrode. Therefore, the selection of negative electrode active materials plays a decisive role in the fast charging capability of lithium-ion batteries. When lithium ions move from the positive electrode to the negative electrode with the electrolyte, the lithium ions will desolvate on the surface of the negative electrode active material, then combine with the active sites on the surface of the negative electrode active material and transfer charge, then pass through the SEI membrane, and finally embed into the negative electrode material particles and diffuse inside the negative electrode material. When the battery charging rate is too high, the active sites on the surface of the negative electrode material are limited, resulting in limited charge transfer rate of lithium ions on the surface of the material. Some lithium ions cannot be embedded in the negative electrode material particles, and they aggregate on the surface of the negative electrode material to generate lithium dendrites, causing the battery impedance to increase and the cycle performance to decrease.
[0003] Although lithium-ion battery performance has made significant breakthroughs in the past few years, judging from the current data on lithium-ion batteries, the lithium-ion battery industry still has certain technical difficulties that have not been overcome, especially the problem that it is difficult to take both the fast charging capability and the cycle performance of lithium-ion batteries into account at the same time. During the battery design stage, a trade-off must be made between the fast charging capability and the cycle performance of lithium-ion batteries. For example, the cycle performance requirements must be lowered when ensuring the high fast charging capability of the battery; conversely, the fast charging standards need to be lowered when ensuring the high cycle performance of the battery. Among all the structural components of the battery, the limitation of the graphite negative electrode material is one of the main reasons for this phenomenon. Summary of the invention
[0004] In order to overcome at least one technical problem existing in the above-mentioned prior art, one of the objects of the present invention is to provide a graphite negative electrode material having both high rate and long cycle performance.
[0005] A second object of the present invention is to provide a method for preparing a graphite negative electrode material.
[0006] A third object of the present invention is to provide a battery.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is:
[0008] The first aspect of the present invention provides a graphite negative electrode material, wherein m 2 The specific surface area in units of 1000 g is recorded as B; the volume median particle size in units of μm of the graphite negative electrode material is recorded as D v50 When the half-cell assembled with the negative electrode and the lithium sheet counter electrode containing the graphite negative electrode material is lithium-inserted at a rate of 2C, the battery remaining capacity SOC when the dQ / dV curve value is first lower than -40mA / V is recorded as S, and the graphite negative electrode material satisfies: 8≤B×D v50 ×S≤24.
[0009] In the present invention, the volume median particle size directly affects the lithium ion diffusion rate in the graphite negative electrode material and the relative volume expansion of the graphite negative electrode material. When the volume median particle size is low, the diffusion path of lithium ions inside the graphite negative electrode material is short, the lithium ion diffusion impedance is low, and the fast charging performance is better, but the small-particle-size graphite negative electrode material will cause the relative volume expansion of lithium insertion to be larger, and the graphite negative electrode material is easily damaged during the cycle, resulting in deterioration of the cycle performance. When the volume median particle size is high, the relative volume expansion of lithium insertion in the graphite negative electrode material is smaller, the graphite structure is more stable during the cycle, and the cycle performance is better, but the large-particle-size graphite negative electrode material will extend the diffusion path of lithium ions inside the graphite negative electrode material, resulting in an increase in lithium ion diffusion impedance and deterioration of the fast charging performance. The graphite negative electrode material provided by the present invention has a moderate volume median particle size and can have both excellent fast charging performance and cycle performance.
[0010] The specific surface area reflects the surface state of the graphite negative electrode material. A good surface structure can help lithium ions quickly embed into the graphite negative electrode material, but the specific surface area also affects the side reaction state of the graphite negative electrode material and the electrolyte. When the specific surface area is small, there are fewer active sites on the surface of the graphite negative electrode material for lithium ion deintercalation, and the desolvation and charge transfer process of lithium ions on the surface of the graphite negative electrode material is slow, and the fast charging ability of the graphite negative electrode material is poor. However, at this time, the side reaction degree of the graphite negative electrode material and the electrolyte is low, and the impedance of the graphite negative electrode material increases slowly during the cycle, and the cycle performance of the graphite negative electrode material is better. When the specific surface area is large, there are more active sites on the surface of the graphite negative electrode material for lithium ion deintercalation, and the desolvation and charge transfer process of lithium ions on the surface of the graphite negative electrode material is fast, and the graphite fast charging ability is better, but at this time, the side reaction degree of the graphite negative electrode material and the electrolyte is high, and the impedance of the graphite negative electrode material increases rapidly during the cycle, and the cycle performance of the graphite negative electrode material is poor. The graphite negative electrode material provided by the present invention has a moderate specific surface area, which ensures sufficient active sites while controlling the degree of side reactions, and can have both excellent fast charging performance and cycle performance.
[0011] In the present invention, the S value is measured by the following test method: the graphite negative electrode material in the present invention is prepared into a negative electrode sheet, and then a button half-cell is assembled with a lithium sheet as a counter electrode, first with 0.1C DC to 0.05V, then with 0.1C CC to 2.5V; then with 2C DC to 100% SOC, to obtain the delithiation capacity Q and the delithiation voltage V, and a dQ / dV curve is made according to the measured delithiation capacity and delithiation voltage data, wherein the abscissa is 0-100% of the battery remaining capacity SOC, and the ordinate is the dQ / dV value, and the SOC when the dQ / dV curve value is lower than -40mA / V for the first time is recorded to obtain the side reaction signal S. The dQ / dV curve of lithium insertion in graphite negative electrode materials reflects the lithium insertion behavior and side reaction behavior of graphite negative electrode materials. At a 2C rate, the intensity of the dQ / dV curve of lithium insertion in graphite negative electrode materials is usually not lower than -35mA / V. When it is lower than -40mA / V, it represents the violent side reaction behavior of the graphite negative electrode material. The later the violent side reaction occurs, the better the fast charging performance of the graphite negative electrode material.
[0012] Preferably, the specific surface area B of the graphite negative electrode material is 0.7 to 3 m 2 / g; Further preferably, the specific surface area B of the graphite negative electrode material is 0.8 to 2m 2 / g. The specific surface area parameter reflects the surface structural characteristics of the graphite negative electrode material. A suitable specific surface area can provide sufficient lithium insertion sites, which is convenient for lithium ion desolvation and charge transfer in the electrolyte, and will not cause excessive side reactions that cause the cycle performance of the graphite negative electrode material to deteriorate. In the present invention, when the specific surface area of the graphite negative electrode material is 0.7 to 3 m 2 / g, it is beneficial to provide sufficient lithium insertion sites, facilitate lithium ion desolvation and charge transfer in the electrolyte, reduce the degree of side reactions, and help improve the cycle performance of graphite negative electrode materials.
[0013] Preferably, the volume median particle size D of the graphite negative electrode material is v50 8 to 16 μm; further preferably, the volume median particle size D of the graphite negative electrode material v50 The volume median particle size reflects the average size of the graphite negative electrode material particles, which directly affects the lithium insertion capacity and relative volume expansion of the graphite negative electrode material, resulting in corresponding changes in the fast charging performance and cycle performance of the graphite negative electrode material. v50 When it is 8 to 16 μm, it is beneficial to improve the lithium insertion capacity of the graphite negative electrode material, reduce the relative volume expansion of the graphite negative electrode material, and is beneficial to improve the fast charging performance and cycle performance of the graphite negative electrode material.
[0014] Preferably, the S>80%; further preferably, the S>85%.
[0015] Preferably, the graphite negative electrode material satisfies: 10≤B×D v50 ×S≤20; further preferably, the graphite negative electrode material satisfies: 13≤B×D v50 ×S≤18.
[0016] Preferably, the raw materials for preparing the graphite negative electrode material include graphite, conductive additives and coal tar pitch.
[0017] Preferably, the conductive additive is selected from at least one of single-walled carbon nanotubes, multi-walled carbon nanotubes, graphene, and conductive carbon black.
[0018] Preferably, the mass ratio of the coal tar pitch to graphite is (2-10):1;
[0019] Preferably, the mass ratio of the graphite to the conductive additive is (8-20):1.
[0020] Preferably, the graphite is flake graphite.
[0021] Preferably, the volume median particle size D of the flake graphite is V50 Less than 1μm.
[0022] Preferably, the preparation method of the flake graphite is: crushing the flake graphite with a sand mill to make the volume median particle size D of the flake graphite V50 Less than 1μm, obtained.
[0023] Preferably, the rotation speed of the sand mill is 1000-3000 r / min.
[0024] Preferably, the crushing time is 0.5 to 2 hours.
[0025] The second aspect of the present invention provides a method for preparing the graphite negative electrode material according to the first aspect of the present invention, comprising the following steps:
[0026] S1: heating and mixing the raw materials for preparing the graphite negative electrode material, and then heating and carbonizing them to obtain a carbonized material;
[0027] S2: Controlling the volume median particle size of the carbonized material, and then heating the carbonized material to graphitize it to obtain the graphite negative electrode material.
[0028] Preferably, step S1 is specifically as follows: heating and mixing coal tar pitch, graphite and a conductive additive to obtain a mixture; heating the mixture under an inert atmosphere for carbonization, and obtaining a carbonized material after cooling; further preferably, step S1 is specifically as follows: heating coal tar pitch to a liquid state, and then mixing it with graphite and a conductive additive to obtain a mixture; heating the mixture under an inert atmosphere for carbonization, and obtaining a carbonized material after cooling.
[0029] Preferably, the step S2 specifically comprises: grinding and crushing the carbonized material to make the volume median particle size of the carbonized material reach 8 to 16 μm, and then heating the carbonized material to graphitize it to obtain the graphite negative electrode material.
[0030] Preferably, in step S1, the temperature of the heating and mixing step is 200-400°C.
[0031] Preferably, in step S1, the heating and mixing step is performed in a stirred reactor.
[0032] Preferably, in step S1, the stirring speed of the heating and mixing step is 30 to 100 r / min.
[0033] Preferably, in step S1, the heating and mixing time is 1 to 3 hours.
[0034] Preferably, in step S1, the temperature of the carbonization is 1000-1500°C.
[0035] Preferably, in step S1, the heating and carbonization time is 1 to 4 hours.
[0036] Preferably, in step S1, the heating rate of the carbonization is 3-6°C / min.
[0037] Preferably, in step S1, the temperature-raising carbonization step is performed under an inert atmosphere.
[0038] Preferably, in step S2, the graphitization step is performed in an Acheson graphitization furnace.
[0039] Preferably, in step S2, the graphitization temperature is 2600-3200°C.
[0040] Preferably, in step S2, the graphitization time is 1 to 4 hours.
[0041] Preferably, in step S2, the heating rate of graphitization is 8-12°C / min.
[0042] Preferably, in step S2, the graphitization step is performed under an inert atmosphere.
[0043] The third aspect of the present invention provides a battery, wherein the negative electrode active material of the battery comprises the graphite negative electrode material described in the first aspect of the present invention.
[0044] Preferably, the battery comprises a lithium ion battery, a sodium ion battery, a potassium ion battery, a zinc ion battery or an aluminum ion battery.
[0045] The beneficial effect of the present invention is that the graphite negative electrode material of the present invention can be obtained by adjusting the volume median particle size Dv50 , specific surface area and S value, so that the three satisfy 8≤B×D v50 ×S≤24, so that the lithium ion battery made of the graphite negative electrode material in the present invention has both high rate and long cycle performance, the polarization degree in the high rate lithium insertion process is low, the lithium precipitation reaction occurs at a later stage, and the fast charging performance is excellent, specifically: at 25°C, the lithium ion battery is fully charged at a 4C rate and fully discharged at a 1C rate for 10 times, and then the lithium ion battery is fully charged at a 4C rate, and there is no lithium precipitation on the surface of the negative electrode plate or only slight lithium precipitation with an area of less than 5% of the lithium precipitation region exists; at 25°C, the lithium ion battery is charged at a 2C rate and discharged at a 1C rate, and the number of cycles in which its capacity decays to 80% of the initial capacity is greater than 2800 cycles. DETAILED DESCRIPTION
[0046] The specific implementation of the present invention is further described in detail below in conjunction with examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that if there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art. The reagents or instruments used that do not indicate the manufacturer are all conventional products that can be purchased commercially.
[0047] In some embodiments of the present invention, the present invention provides a graphite negative electrode material, wherein m of the graphite negative electrode material is 2 The specific surface area in units of / g is recorded as B; the volume median particle size in units of μm of the graphite negative electrode material is recorded as D v50 ; When the half-cell assembled with the negative electrode and the lithium sheet counter electrode containing the graphite negative electrode material is lithium-inserted at a 2C rate, the battery remaining capacity SOC when the dQ / dV curve value is lower than -40mA / V for the first time is recorded as S, then the graphite negative electrode material satisfies: 8≤B×D v50 ×S≤24.
[0048] After conducting a large number of experiments on graphite negative electrode materials, the inventors found that when the specific surface area and volume median particle size of the graphite negative electrode material are controlled within a reasonable range, and the dQ / dV curve value of the graphite negative electrode material in the 2C rate lithium insertion test of the button half-cell is less than -40mA / V for the first time, the SOC corresponding to the SOC reaches a certain value, that is, 8≤B×D v50 When ×S≤24, the lithium-ion battery made of the graphite negative electrode material has better fast charging performance and cycle performance.
[0049] In the present invention, if the specific surface area B of the graphite negative electrode material is too large, resulting in B×D v50When the value of ×S is greater than 24, the cycle performance of the lithium-ion battery is poor. The reason is that the specific surface area B of the graphite negative electrode material is too large, which will lead to an increase in the side reactions between the electrolyte and the graphite negative electrode material, and excessive consumption of active lithium during the battery cycle, resulting in a decrease in battery capacity. If the specific surface area B of the graphite negative electrode material is too small, B×D v50 When the value of ×S is lower than 8, the fast charging performance of the lithium-ion battery is poor. The reason is: when the specific surface area B of the graphite negative electrode material is too small, there are fewer defects and pores on the surface of the graphite negative electrode material, resulting in relatively fewer active sites on the surface of the graphite negative electrode material for lithium ion embedding, which is not conducive to the rapid charge transfer of lithium ions on the surface of the graphite negative electrode material, and the fast charging performance of the battery is poor.
[0050] If the volume median particle size D of the graphite negative electrode material v50 Too small leads to B×D v50 When the value of ×S is less than 8, the cycle performance of lithium-ion batteries is poor. The reason is that the volume median particle size D of the graphite negative electrode material is v50 If the volume median particle size D of the graphite anode material is too small, the relative volume expansion of the graphite anode material will be large during the lithium insertion process, and the particles will be seriously damaged during the long cycle, resulting in a decrease in the battery cycle performance. v50 Too big leads to B×D v50 When the value of ×S is greater than 24, the fast charging performance of lithium-ion batteries is poor. The reason is that the volume median particle size D of the graphite negative electrode material is v50 Too much length will extend the diffusion path of lithium ions inside the graphite negative electrode material, resulting in a higher lithium ion diffusion impedance of the graphite negative electrode material, which is not conducive to fast charging of the battery.
[0051] If the side reaction signal S is too small, B×D v50 When the value of ×S is less than 8, the fast charging performance of the lithium-ion battery is poor. The reason is that when the side reaction signal S of graphite is too small, the polarization of the graphite negative electrode is large, and lithium dendrites are generated in the early stage of battery charging, resulting in reversible lithium consumption, increased impedance, and deterioration of fast charging performance.
[0052] Therefore, the inventors have found through extensive research that the volume median particle size D of the graphite negative electrode material is v50 There is a mutual restraint relationship between the specific surface area B and the side reaction signal S, which jointly affect the fast charging performance and cycle performance of the graphite negative electrode material. Only when the volume median particle size D of the graphite negative electrode material is v50 , specific surface area B and side reaction signal S satisfy: 8≤B×D v50 When ×S≤24, the comprehensive performance of lithium-ion batteries is better, and they also have good fast charging performance and cycle performance.
[0053] The dQ / dV curve of lithium insertion in graphite negative electrode materials reflects the lithium insertion behavior and side reaction behavior of graphite negative electrode materials. At a 2C rate, the intensity of the dQ / dV curve of lithium insertion in graphite negative electrode materials is usually not lower than -35mA / V. When it is lower than -40mA / V, it represents the violent side reaction behavior of the graphite negative electrode material. The later the violent side reaction occurs, the better the fast charging performance of the graphite negative electrode material.
[0054] In some embodiments of the present invention, the specific surface area B of the graphite negative electrode material is 0.7 to 3 m 2 / g, for example, can be selected from 0.7m 2 / g, 0.8m 2 / g, 0.9m 2 / g, 1m 2 / g, 1.1m 2 / g, 1.2m 2 / g, 1.3m 2 / g, 1.4m 2 / g, 1.5m 2 / g, 1.6m 2 / g, 1.7m 2 / g, 1.8m 2 / g, 1.9m 2 / g, 2m 2 / g, 2.1m 2 / g, 2.2m 2 / g, 2.3m 2 / g, 2.4m 2 / g, 2.5m 2 / g, 2.6m 2 / g, 2.7m 2 / g, 2.8m 2 / g, 2.9m 2 / g, 3m 2 / g or any point value in the range composed of the above two end points; in some embodiments of the present invention, the specific surface area B of the graphite negative electrode material is 0.8 to 2m 2 / g. The specific surface area of graphite negative electrode materials is usually positively correlated with the number of active sites on the surface of graphite negative electrode materials. The larger the specific surface area, the more active sites on the surface of graphite negative electrode materials, which is more conducive to the desolvation and charge transfer of lithium ions on the surface of graphite negative electrode materials, and is beneficial to the improvement of the fast charging performance of the battery cell. At the same time, a larger specific surface area will also lead to an increase in side reactions between graphite negative electrode materials and electrolytes. During the battery cycle, side reactions will lead to the thickening of SEI on the surface of graphite negative electrode materials and an increase in impurities in the electrolyte, resulting in reversible lithium loss and a decrease in battery cycle performance. In view of this, the inventors have found through a lot of research that when the specific surface area of the graphite negative electrode material is controlled between 0.7 and 3m 2 / g range, both fast charging performance and long cycle performance can be taken into account.
[0055] In some embodiments of the present invention, the volume median particle size D of the graphite negative electrode material is v50 is 8 to 16 μm, for example, it can be selected from 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm or any point in the range composed of the above two end points; in some embodiments of the present invention, the volume median particle size D of the graphite negative electrode material v50 It is 10 to 12 μm. The volume median particle size affects the diffusion path of lithium ions in the graphite negative electrode material particles. Under the same mass, the lower the volume median particle size of the graphite negative electrode material, the shorter the lithium ion diffusion path, the lower the diffusion impedance, and the better the fast charging capability. However, the graphite negative electrode material with a smaller volume median particle size has a greater relative volume expansion when lithium is inserted. During the charge and discharge process, the large volume change causes serious damage to the particles, destroying the stable structure and causing the battery cycle performance to decline. Therefore, the volume median particle size of the graphite negative electrode material provided by the present invention is 8 to 16 μm, taking into account good fast charging and cycle performance.
[0056] In some embodiments of the present invention, S>80%, for example, the value of S can be selected from: 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 100% or any point in the range formed by the above two end points; in some embodiments of the present invention, S>85%.
[0057] In the present invention, the graphite negative electrode material satisfies: 8≤B×D v50 ×S≤24, for example: B×D of graphite negative electrode material v50 The value of ×S can be selected from 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24 or any point in the range formed by the above two end points. In some preferred embodiments of the present invention, the graphite negative electrode material satisfies: 10≤B×D v50 ×S≤20; In some preferred embodiments of the present invention, the graphite negative electrode material satisfies: 13≤B×D v50 ×S≤18. When the graphite negative electrode material meets the above requirements, the lithium-ion battery can have better fast charging performance and cycle performance.
[0058] In some embodiments of the present invention, the raw material for preparing the graphite negative electrode material is selected from at least one of graphite, coal tar pitch, carbon nanotubes, coconut shells, phenolic resins, epoxy resins, glucose, sucrose, and starch.
[0059] In some embodiments of the present invention, the raw materials for preparing the graphite negative electrode material include graphite, a conductive additive and coal tar pitch.
[0060] In some embodiments of the present invention, the conductive additive is selected from at least one of single-walled carbon nanotubes, multi-walled carbon nanotubes, graphene, and conductive carbon black.
[0061] In some embodiments of the present invention, the mass ratio of coal tar pitch and graphite is (2-10):1, for example, it can be selected from 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1 or any point value in the range composed of the above two end points.
[0062] In some embodiments of the present invention, the mass ratio of graphite to the conductive additive is (8-20):1, for example, it can be selected from 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, 19:1, 20:1 or any point value in the range composed of the above two end points.
[0063] In some embodiments of the present invention, the graphite is flake graphite.
[0064] In some embodiments of the present invention, the volume median particle size D of the flake graphite V50 Less than 1μm.
[0065] In some embodiments of the present invention, the method for preparing flake graphite is: crushing the flake graphite with a sand mill to make the volume median particle size D of the flake graphite V50 Less than 1μm, obtained.
[0066] In some embodiments of the present invention, the rotation speed of the sand mill is 1000-3000 r / min, for example, it can be selected from 1000 r / min, 1500 r / min, 2000 r / min, 2500 r / min, 3000 r / min or any point value in the range composed of the above two end points.
[0067] In some embodiments of the present invention, the fragmentation time is 0.5 to 2 h, for example, it can be selected from 0.5 h, 0.6 h, 0.7 h, 0.8 h, 0.9 h, 1 h, 1.1 h, 1.2 h, 1.3 h, 1.4 h, 1.5 h, 1.6 h, 1.7 h, 1.8 h, 1.9 h, 2 h or any point value in the range formed by the above two end points.
[0068] In some embodiments of the present invention, the present invention also provides a method for preparing a graphite negative electrode material, comprising the following steps:
[0069] S1: heating and mixing the raw materials for preparing the graphite negative electrode material, and then heating and carbonizing them to obtain a carbonized material;
[0070] S2: Controlling the volume median particle size of the carbonized material, and then heating the carbonized material to graphitize it to obtain a graphite negative electrode material.
[0071] In some embodiments of the present invention, step S1 specifically comprises: heating coal tar pitch, graphite, and a conductive additive to obtain a mixture; heating the mixture to carbonize under an inert atmosphere, and cooling the mixture to obtain a carbonized material. In some embodiments of the present invention, step S1 specifically comprises: heating coal tar pitch to a liquid state, and then mixing it with graphite and a conductive additive to obtain a mixture; heating the mixture to carbonize under an inert atmosphere, and cooling the mixture to obtain a carbonized material.
[0072] In some embodiments of the present invention, step S2 specifically comprises: grinding and crushing the carbonized material to make the volume median particle size of the carbonized material reach 8 to 16 μm, and then heating the carbonized material to graphitize it to obtain a graphite negative electrode material.
[0073] In some embodiments of the present invention, in step S1, the temperature of the heating mixing step is 200-400°C, for example, it can be selected from 200°C, 220°C, 240°C, 260°C, 280°C, 300°C, 320°C, 340°C, 360°C, 380°C, 400°C or any point value in the range composed of the above two end points.
[0074] In some embodiments of the present invention, in step S1, the heating and mixing step is performed in a stirred reactor.
[0075] In some embodiments of the present invention, in step S1, the stirring speed of the heating mixing step is 30 to 100 r / min, for example, it can be selected from 30 r / min, 40 r / min, 50 r / min, 60 r / min, 70 r / min, 80 r / min, 90 r / min, 100 r / min or any point value in the range composed of the above two end points.
[0076] In some embodiments of the present invention, in step S1, the heating mixing time is 1 to 3 hours, for example, it can be selected from 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours or any point value in the range consisting of the above two end points.
[0077] In some embodiments of the present invention, in step S1, the temperature of heating and carbonization is 1000-1500°C, for example, it can be selected from 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, 1500°C or any point in the range composed of the above two end points.
[0078] In some embodiments of the present invention, in step S1, the heating and carbonization time is 1 to 4 hours, for example, it can be selected from 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours or any point value in the range formed by the above two end points.
[0079] In some embodiments of the present invention, in step S1, the heating rate of carbonization is 3 to 6°C / min, for example, it can be selected from 3°C / min, 4°C / min, 5°C / min, 6°C / min or any point value in the range composed of the above two end points.
[0080] In some embodiments of the present invention, in step S1, the temperature-raising carbonization step is performed under an inert atmosphere.
[0081] In some embodiments of the present invention, in step S2, the graphitization step is performed in an Acheson graphitization furnace.
[0082] In some embodiments of the present invention, in step S2, the graphitization temperature is 2600-3200°C, for example, it can be selected from 2600°C, 2700°C, 2800°C, 2900°C, 3000°C, 3100°C, 3200°C or any point in the range composed of the above two end points.
[0083] In some embodiments of the present invention, in step S2, the graphitization time is 1 to 4 hours, for example, it can be selected from 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours or any point in the range consisting of the above two end points.
[0084] In some embodiments of the present invention, in step S2, the heating rate of graphitization is 8 to 12°C / min, for example, it can be selected from 8°C / min, 9°C / min, 10°C / min, 11°C / min, 12°C / min or any point value in the range composed of the above two end points.
[0085] In some embodiments of the present invention, in step S2, the graphitization step is performed under an inert atmosphere.
[0086] In some embodiments of the present invention, the present invention further provides a lithium ion battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the negative electrode active material of the negative electrode of the lithium ion battery comprises the above-mentioned graphite negative electrode material.
[0087] In some embodiments of the present invention, the negative electrode active material further includes a conductive agent and a binder.
[0088] In some embodiments of the present invention, the mass ratio of the graphite negative electrode material, the conductive agent and the binder is (40-50):1:(1-5).
[0089] In some embodiments of the present invention, the binder is selected from at least one of polyacrylic acid, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyvinyl alcohol, carboxymethyl cellulose, sodium carboxymethyl cellulose, polyimide, polyamide-imide, styrene-butadiene rubber, and polyvinylidene fluoride.
[0090] In some embodiments of the present invention, the conductive agent is selected from at least one of conductive carbon black, acetylene black, Ketjen black, graphene, carbon fiber, single-walled carbon nanotubes, and multi-walled carbon nanotubes.
[0091] In some embodiments of the present invention, the separator includes at least one of polyethylene and polypropylene.
[0092] In some embodiments of the present invention, the electrolyte is a non-aqueous electrolyte, and the non-aqueous electrolyte includes a carbonate solvent and a lithium salt. In some embodiments of the present invention, the carbonate solvent includes at least one of ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), fluoroethylene carbonate (FEC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC). In some embodiments of the present invention, the lithium salt includes at least one of LiPF6, LiBF4, LiSbF6, LiClO4, LiCF3SO3, LiAlO4, LiAlCl4, Li(CF3SO2)2N, LiBOB, and LiDFOB.
[0093] In some embodiments of the present invention, the positive electrode active material in the positive electrode is selected from nickel-cobalt-manganese ternary materials.
[0094] The specific surface area B and volume median particle size D of the graphite negative electrode material in the present invention are v50 , dQ / dV side reaction signal S data is tested using the following test method:
[0095] (1) Specific surface area B: The specific surface area was measured using a Micromeritics tristar II 3020N2 adsorption-desorption instrument. Sample pretreatment conditions: treatment temperature 300°C, treatment time 3 hours, nitrogen as the adsorption gas, liquid nitrogen as the cooling medium, the quantitative relationship between the monolayer saturated adsorption amount and the multilayer adsorption amount was fitted by the BET equation, and the specific surface area of graphite was calculated according to the multi-point BET method.
[0096] (2) Volume median particle size D v50: Obtained by using a laser diffraction particle size analyzer (MS2000), the sample particles are dispersed in a liquid medium at a concentration of 200-300 mg / L, and a monochromatic light beam is passed through. After the light is scattered by the particles, it is distributed at different angles. The regular multi-element detector receives the values of the scattering diagram at many angles and records these values for analysis. Using the Rayleigh scattering formula, the scattering values are calculated to obtain the ratio of the volume of particles of each size level to the total volume, thereby obtaining the volume median particle diameter D v50 .
[0097] (3) Side reaction signal S: The negative electrode sheet is prepared by using graphite negative electrode material as the negative electrode active material and then assembled with the lithium sheet into a button-type half-cell battery. The side reaction signal test is then carried out according to the following steps: (1) 0.1C DC to 0.05V; (2) 0.1C CC to 2.5V; (3) 2C DC to 100% SOC. After the test is completed, the de-lithiation capacity Q and de-lithiation voltage V are obtained. A dQ / dV curve is drawn based on the measured de-lithiation capacity and de-lithiation voltage data, where the horizontal axis is 0-100% battery remaining capacity SOC, and the vertical axis is the dQ / dV value. The SOC when the dQ / dV curve value first drops below -40mA / V is recorded to obtain the side reaction signal S.
[0098] The electrolyte used in the side reaction signal S test is a LiPF6 solution with a concentration of 1 mol / L, and the solvent of the electrolyte is a mixed solvent of ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) in a volume ratio of 1:1:1.
[0099] The implementation of the present invention is further described in detail below with reference to specific embodiments:
[0100] Example 1
[0101] This example provides a graphite negative electrode material, which is prepared by the following preparation method:
[0102] Prepare graphite flakes (particle size of 15 μm), single-walled carbon nanotubes, and coal tar pitch (softening temperature of 250° C.) to prepare graphite negative electrode materials according to the following steps:
[0103] S1: placing flake graphite in a horizontal sand mill and crushing it at a speed of 2000 r / min for 1 h to obtain flake graphite fine powder with a particle size of 0.5 μm;
[0104] S2: 5 kg of coal tar pitch was placed in a stirred reactor, and the reactor was heated to 300° C. until the coal tar pitch was completely liquefied, and then 1 kg of flake graphite fine powder and 0.1 kg of single-walled carbon nanotubes were added to the stirred reactor, and mixed at a speed of 60 r / min for 2 h to obtain a mixture;
[0105] S3: transferring the mixture in step S2 into a tube furnace, heating it to 1200° C. at a heating rate of 5° C. / min under an argon atmosphere and keeping the temperature for 2 h, and obtaining a carbonized material after natural cooling;
[0106] S4: crushing the carbonized material in step S3 into a particle size of 8 μm to obtain a semi-finished product powder;
[0107] S5: The semi-finished powder in step S4 is transferred to an Acheson graphitization furnace, heated to 3000°C at a heating rate of 10°C / min under an argon atmosphere and kept warm for 2 hours, and then taken out after natural cooling to obtain the graphite negative electrode material in this example.
[0108] According to the test method described in the present invention, the D of the graphite negative electrode material prepared in this example is v50 The specific surface area B is 1.9 m 2 / g, side reaction signal S is 82.3%, B×D v50 The value of ×S is 12.5, as shown in Table 1.
[0109] Example 2
[0110] The preparation method of the graphite negative electrode material in this example is different from that in Example 1 only in that in step S4 of this example, the particle size of the semi-finished powder after the carbonized material is crushed is 10 μm.
[0111] According to the test method described in the present invention, the D of the graphite negative electrode material prepared in this example is v50 , specific surface area B, side reaction signal S, B×D v50 The specific values of ×S are shown in Table 1.
[0112] Example 3
[0113] The preparation method of the graphite negative electrode material in this example is different from that in Example 1 only in that in step S4 of this example, the particle size of the semi-finished powder after the carbonized material is crushed is 12 μm.
[0114] According to the test method described in the present invention, the D of the graphite negative electrode material prepared in this example is v50 , specific surface area B, side reaction signal S, B×D v50 The specific values of ×S are shown in Table 1.
[0115] Example 4
[0116] The preparation method of the graphite negative electrode material in this example is different from that in Example 1 only in that in step S4 of this example, the particle size of the semi-finished powder after the carbonized material is crushed is 14 μm.
[0117] According to the test method described in the present invention, the D of the graphite negative electrode material prepared in this example is v50 , specific surface area B, side reaction signal S, B×D v50 The specific values of ×S are shown in Table 1.
[0118] Example 5
[0119] The preparation method of the graphite negative electrode material in this example is different from that in Example 1 only in that in step S4 of this example, the particle size of the semi-finished powder after the carbonized material is crushed is 16 μm.
[0120] According to the test method described in the present invention, the D of the graphite negative electrode material prepared in this example is v50 , specific surface area B, side reaction signal S, B×D v50 The specific values of ×S are shown in Table 1.
[0121] Example 6
[0122] The preparation method of the graphite negative electrode material in this example is different from that in Example 1 only in that: in step S4 of this example, the particle size of the semi-finished powder after the carbonized material is crushed is 13 μm; in step S5, the graphitization temperature of the semi-finished powder is 3200°C.
[0123] According to the test method described in the present invention, the D of the graphite negative electrode material prepared in this example is v50 , specific surface area B, side reaction signal S, B×D v50 The specific values of ×S are shown in Table 1.
[0124] Example 7
[0125] The preparation method of the graphite negative electrode material in this example is different from that in Example 1 only in that: in step S4 of this example, the particle size of the semi-finished powder after the carbonized material is crushed is 13 μm; in step S5, the graphitization temperature of the semi-finished powder is 3100°C.
[0126] According to the test method described in the present invention, the D of the graphite negative electrode material prepared in this example is v50 , specific surface area B, side reaction signal S, B×D v50 The specific values of ×S are shown in Table 1.
[0127] Example 8
[0128] The preparation method of the graphite negative electrode material in this example is different from that in Example 1 only in that in step S4 of this example, the particle size of the semi-finished powder after the carbonized material is crushed is 13 μm.
[0129] According to the test method described in the present invention, the D of the graphite negative electrode material prepared in this example isv50 , specific surface area B, side reaction signal S, B×D v50 The specific values of ×S are shown in Table 1.
[0130] Example 9
[0131] The preparation method of the graphite negative electrode material in this example is different from that in Example 1 only in that: in step S4 of this example, the particle size of the semi-finished powder after the carbonized material is crushed is 13 μm; in step S5, the graphitization temperature of the semi-finished powder is 2800°C.
[0132] According to the test method described in the present invention, the D of the graphite negative electrode material prepared in this example is v50 , specific surface area B, side reaction signal S, B×D v50 The specific values of ×S are shown in Table 1.
[0133] Example 10
[0134] The preparation method of the graphite negative electrode material in this example is different from that in Example 1 only in that: in step S4 of this example, the particle size of the semi-finished powder after the carbonized material is crushed is 13 μm; in step S5, the graphitization temperature of the semi-finished powder is 2600°C.
[0135] According to the test method described in the present invention, the D of the graphite negative electrode material prepared in this example is v50 , specific surface area B, side reaction signal S, B×D v50 The specific values of ×S are shown in Table 1.
[0136] Embodiment 11
[0137] The preparation method of the graphite negative electrode material in this example is different from that in Example 1 only in that: in step S2 of this example, the amount of flake graphite fine powder added is 1.4 kg; in step S4, the particle size of the semi-finished powder after the carbonized material is crushed is 13 μm.
[0138] According to the test method described in the present invention, the D of the graphite negative electrode material prepared in this example is v50 , specific surface area B, side reaction signal S, B×D v50 The specific values of ×S are shown in Table 1.
[0139] Example 12
[0140] The preparation method of the graphite negative electrode material in this example is different from that in Example 1 only in that: in step S2 of this example, the amount of flake graphite fine powder added is 0.9 kg; in step S4, the particle size of the semi-finished powder after the carbonized material is crushed is 13 μm.
[0141] According to the test method described in the present invention, the D of the graphite negative electrode material prepared in this example is v50 , specific surface area B, side reaction signal S, B×D v50 The specific values of ×S are shown in Table 1.
[0142] Embodiment 13
[0143] The preparation method of the graphite negative electrode material in this example is different from that in Example 1 only in that: in step S2 of this example, the amount of flake graphite fine powder added is 0.8 kg; in step S4, the particle size of the semi-finished powder after the carbonized material is crushed is 13 μm.
[0144] According to the test method described in the present invention, the D of the graphite negative electrode material prepared in this example is v50 , specific surface area B, side reaction signal S, B×D v50 The specific values of ×S are shown in Table 1.
[0145] Embodiment 14
[0146] The preparation method of the graphite negative electrode material in this example is different from that in Example 1 only in that: in step S2 of this example, the addition amount of flake graphite fine powder is 0.7 kg; in step S4, the particle size of the semi-finished powder after the carbonized material is crushed is 13 μm.
[0147] According to the test method described in the present invention, the D of the graphite negative electrode material prepared in this example is v50 , specific surface area B, side reaction signal S, B×D v50 The specific values of ×S are shown in Table 1.
[0148] Embodiment 15
[0149] The preparation method of the graphite negative electrode material in this example is different from that in Example 1 only in that: in step S2 of this example, the addition amount of flake graphite fine powder is 0.6 kg; in step S4, the particle size of the semi-finished powder after the carbonized material is crushed is 13 μm.
[0150] According to the test method described in the present invention, the D of the graphite negative electrode material prepared in this example is v50 , specific surface area B, side reaction signal S, B×D v50 The specific values of ×S are shown in Table 1.
[0151] Comparative Example 1
[0152] The preparation method of the graphite negative electrode material in this example is different from that in Example 1 only in that in step S4 of this example, the particle size of the semi-finished powder after the carbonized material is crushed is 7 μm.
[0153] According to the test method described in the present invention, the D of the graphite negative electrode material prepared in this example is v50 , specific surface area B, side reaction signal S, B×D v50 The specific values of ×S are shown in Table 1.
[0154] Comparative Example 2
[0155] The preparation method of the graphite negative electrode material in this example is different from that in Example 1 only in that in step S4 of this example, the particle size of the semi-finished powder after the carbonized material is crushed is 19 μm.
[0156] According to the test method described in the present invention, the D of the graphite negative electrode material prepared in this example is v50 , specific surface area B, side reaction signal S, B×D v50 The specific values of ×S are shown in Table 1.
[0157] Comparative Example 3
[0158] The preparation method of the graphite negative electrode material in this example is different from that in Example 1 only in that: in step S4 of this example, the particle size of the semi-finished powder after the carbonized material is crushed is 14 μm; in step S5, the graphitization temperature of the semi-finished powder is 2400°C.
[0159] According to the test method described in the present invention, the D of the graphite negative electrode material prepared in this example is v50 , specific surface area B, side reaction signal S, B×D v50 The specific values of ×S are shown in Table 1.
[0160] Comparative Example 4
[0161] The preparation method of the graphite negative electrode material in this example is different from that in Example 1 only in that: in step S4 of this example, the particle size of the semi-finished powder after the carbonized material is crushed is 14 μm; in step S5, the graphitization temperature of the semi-finished powder is 3400°C.
[0162] According to the test method described in the present invention, the D of the graphite negative electrode material prepared in this example is v50 , specific surface area B, side reaction signal S, B×D v50 The specific values of ×S are shown in Table 1.
[0163] Comparative Example 5
[0164] The preparation method of the graphite negative electrode material in this example is different from that in Example 1 only in that: in step S2 of this example, single-walled carbon nanotubes are not added; in step S4, the particle size of the semi-finished powder after the carbonized material is crushed is 10 μm.
[0165] According to the test method described in the present invention, the D of the graphite negative electrode material prepared in this example is v50 , specific surface area B, side reaction signal S, B×D v50 The specific values of ×S are shown in Table 1.
[0166] The graphite negative electrode materials in Examples 1 to 15 and Comparative Examples 1 to 5 are respectively prepared into lithium-ion batteries, the structure of which includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, wherein the negative electrode sheet is loaded with the graphite negative electrode materials prepared in Examples 1 to 15 and Comparative Examples 1 to 5.
[0167] The preparation method of lithium-ion battery is as follows:
[0168] (1) Preparation of positive electrode sheet
[0169] The positive electrode active material NCM811, the conductive agent carbon nanotubes, and the binder PVDF are mixed in a mass ratio of 94:3:4, and the solvent NMP is added, and the mixture is stirred evenly to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on both sides of the positive electrode collector aluminum foil, dried in an oven, and then cold pressed and cut to obtain a positive electrode sheet.
[0170] (2) Preparation of negative electrode sheet
[0171] First, prepare the negative electrode slurry: add 70% carboxymethyl cellulose (CMC) and conductive carbon black into deionized water, stir at a speed of 1000r / min for 2h to form a conductive glue; add the graphite negative electrode material prepared in the embodiment or comparative example into the conductive glue, stir at a speed of 1500r / min for 1h to form a first mixed solution; add styrene-butadiene rubber (SBR) into the first mixed solution, stir at a speed of 1500r / min for 1h to form a second mixed solution; add ethanol and the remaining 30% of CMC powder into the second mixed solution, stir at a speed of 1500r / min for 2h to prepare the negative electrode slurry. In the negative electrode slurry, the mass ratio of graphite negative electrode material, conductive carbon black, CMC, and SBR is 93:2:2:3, the volume ratio of deionized water to ethanol is 9:1, and the solid content of the negative electrode slurry is 50%;
[0172] Secondly, prepare the negative electrode sheet: evenly apply the negative electrode slurry on both sides of the negative electrode collector copper foil, dry it in an oven, and then obtain the negative electrode sheet after cold pressing and slitting.
[0173] (3) Preparation of electrolyte
[0174] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed at a volume ratio of 1:1:1 to obtain an organic solvent, and then fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent at a concentration of 1 mol / L to obtain an electrolyte after full dissolution.
[0175] (4) Preparation of isolation membrane
[0176] A polyethylene film was selected as the separator.
[0177] (5) Preparation of lithium-ion batteries
[0178] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, with the separator being between the positive electrode sheet and the negative electrode sheet, and the separator plays an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.
[0179] Performance Test:
[0180] The performance of lithium-ion batteries prepared using the graphite negative electrode materials in Examples 1 to 15 and Comparative Examples 1 to 5 was tested respectively according to the following test methods:
[0181] (1) Dynamic performance test: At 25°C, the lithium-ion battery was fully charged at a rate of 4C and fully discharged at a rate of 1C for 10 times, and then the lithium-ion battery was fully charged at a rate of 4C, and then the negative electrode was disassembled and the lithium deposition on the surface of the negative electrode was observed. Among them, the area of lithium deposition on the surface of the negative electrode is less than 5%, which is considered to be slight lithium deposition, the area of lithium deposition on the surface of the negative electrode is 5% to 40%, which is considered to be moderate lithium deposition, and the area of lithium deposition on the surface of the negative electrode is greater than 40%, which is considered to be severe lithium deposition.
[0182] (2) Cycle performance test: At 25°C, the lithium-ion battery was charged at a 2C rate and discharged at a 1C rate, and a full charge and discharge cycle test was performed until the capacity of the lithium-ion battery decayed to 80% of the initial capacity, and the number of cycles at this time was recorded.
[0183] The performance of lithium-ion batteries made from the graphite negative electrode materials in Examples 1 to 15 and Comparative Examples 1 to 5 measured according to the above test method is shown in Table 1 below.
[0184] Table 1 Performance data of graphite negative electrode materials and performance data of lithium-ion batteries
[0185]
[0186] As can be seen from Table 1, the graphite negative electrode material in the present invention satisfies 8≤B×D v50×S≤24, the kinetic performance and cycle performance of the lithium-ion battery made from the graphite negative electrode material of the present invention are both excellent, with both fast charging and high cycle performance, specifically: at 25°C, the lithium-ion battery is fully charged at a 4C rate and fully discharged at a 1C rate for 10 times, and then the lithium-ion battery is fully charged at a 4C rate, and there is no lithium deposition on the surface of the negative electrode plate or there is only slight lithium deposition with an area of less than 5% of the lithium deposition area; at 25°C, the lithium-ion battery is charged at a 2C rate and discharged at a 1C rate, and the number of cycles in which its capacity decays to 80% of the initial capacity is greater than 2800. The reason why the lithium-ion battery made from the graphite negative electrode material of the present invention has both fast charging and high cycle performance is that the graphite negative electrode material of the present invention has good particle size, particle internal structure and surface state, has better lithium insertion channels, low lithium insertion expansion and abundant active sites, and the specific analysis is as follows:
[0187] When the volume median particle size D of the graphite negative electrode material v50 Too low leads to B×D v50 When ×S is less than 8 (such as Comparative Example 1), the cycle performance of the lithium-ion battery is poor. The reason is that when the volume median particle size D v50 If the relative volume of the graphite negative electrode material expands greatly during the lithium insertion process, the structural damage during the lithium ion battery cycle is more serious, resulting in a decrease in the internal lithium storage space and a decrease in the battery capacity. Therefore, the number of cycles of the lithium ion battery in Comparative Example 1 is only 2110.
[0188] When the volume median particle size D of the graphite negative electrode material v50 Too high leads to B×D v50 When ×S is greater than 24 (such as Comparative Example 2), the fast charging capability of the lithium-ion battery is poor. The reason is that when the volume median particle size D v50 If the temperature is too high, the lithium ion diffusion path of the graphite negative electrode material when embedded with lithium is longer, the lithium ion diffusion impedance is higher, and the lithium ions on the surface of the graphite negative electrode material are not easy to be deeply embedded in the particles, causing the lithium ions to aggregate on the surface of the graphite negative electrode material and generate lithium dendrites. Therefore, the kinetic performance test result of Comparative Example 2 is severe lithium precipitation.
[0189] When the specific surface area B of the graphite negative electrode material is too high, B×D v50 When ×S is greater than 24 (such as Comparative Example 3), the cycle performance of the lithium-ion battery is poor. The reason is that when the specific surface area B of the graphite negative electrode material is high, the contact area between the graphite negative electrode material and the electrolyte is large, and there are more side reactions between the graphite negative electrode material and the electrolyte during the charge and discharge process of the lithium-ion battery. With the charge and discharge cycle of the battery, active lithium is continuously lost, and the battery capacity retention rate decreases. Therefore, the number of cycles of the lithium-ion battery in Comparative Example 3 is only 1863.
[0190] When the specific surface area B of the graphite negative electrode material is too low, B×D v50 When ×S is lower than 8 (such as Comparative Example 4), the fast charging performance of the lithium-ion battery is poor. The reason is that when the specific surface area B of the graphite negative electrode material is low, there are fewer defects and pores on the surface of the graphite negative electrode material, and there are fewer active sites on the surface of the graphite negative electrode material for lithium ion embedding. Under high-rate charging conditions, lithium ions cannot be embedded in the graphite negative electrode material in time and gather on the surface of the graphite negative electrode material to form lithium dendrites. Therefore, the kinetic performance test result of Comparative Example 4 is severe lithium precipitation.
[0191] When the side reaction signal S is too low, B×D v50 When ×S is lower than 8 (such as Comparative Example 5), the fast charging performance of the lithium-ion battery is poor. The reason is that the lower side reaction signal S reflects the higher impedance and polarization of the graphite negative electrode material, the lithium dendrites are generated at the beginning of charging, and the fast charging performance is poor. Therefore, the kinetic performance test result of Comparative Example 5 is severe lithium precipitation.
[0192] In summary, the graphite negative electrode material in the present invention is obtained by adjusting the volume median particle size D v50 , specific surface area and S value, so that the three satisfy 8≤B×D v50 ×S≤24, so that the lithium ion battery made of the graphite negative electrode material in the present invention has both high rate and long cycle performance, the polarization degree in the high rate lithium insertion process is low, the lithium precipitation reaction occurs at a later stage, and the fast charging performance is excellent, specifically: at 25°C, the lithium ion battery is fully charged at a 4C rate and fully discharged at a 1C rate for 10 times, and then the lithium ion battery is fully charged at a 4C rate, and there is no lithium precipitation on the surface of the negative electrode plate or only slight lithium precipitation with an area of less than 5% of the lithium precipitation region exists; at 25°C, the lithium ion battery is charged at a 2C rate and discharged at a 1C rate, and the number of cycles in which its capacity decays to 80% of the initial capacity is greater than 2800 cycles.
[0193] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A graphite negative electrode material, characterized in that: The graphite negative electrode material m 2 The specific surface area in units of 1000 g is recorded as B; the volume median particle size in units of μm of the graphite negative electrode material is recorded as D v50 When the half-cell assembled with the negative electrode and the lithium sheet counter electrode containing the graphite negative electrode material is lithium-inserted at a rate of 2C, the battery remaining capacity SOC when the dQ / dV curve value is first lower than -40mA / V is recorded as S, and the graphite negative electrode material satisfies: 8≤B×D v50 ×S≤24.
2. The graphite negative electrode material according to claim 1, characterized in that: The specific surface area B of the graphite negative electrode material is 0.7 to 3 m 2 / g.
3. The graphite negative electrode material according to claim 1, characterized in that: The volume median particle size D of the graphite negative electrode material v50 8~16μm.
4. The graphite negative electrode material according to claim 1, characterized in that: The S>80%.
5. The graphite negative electrode material according to any one of claims 1 to 4, characterized in that: The graphite negative electrode material satisfies: 10≤B×D v50 ×S≤20.
6. The graphite negative electrode material according to claim 1, characterized in that: The raw materials for preparing the graphite negative electrode material include graphite, conductive additives and coal tar pitch.
7. The method for preparing the graphite negative electrode material according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1: heating and mixing the raw materials for preparing the graphite negative electrode material, and then heating and carbonizing them to obtain a carbonized material; S2: Controlling the volume median particle size of the carbonized material, and then heating the carbonized material to graphitize it to obtain the graphite negative electrode material.
8. The method for preparing a graphite negative electrode material according to claim 7, characterized in that: In step S1, the temperature of heating and carbonization is 1000-1500°C; And / or, in step S1, the heating and carbonization time is 1 to 4 hours; And / or, in step S1, the heating rate of the carbonization is 3-6°C / min; And / or, in step S1, the temperature-raising carbonization step is performed under an inert atmosphere; And / or, in step S2, the graphitization temperature is 2600-3200°C; And / or, in step S2, the graphitization time is 1 to 4 hours; And / or, in step S2, the heating rate of graphitization is 8-12°C / min; And / or, in step S2, the graphitization step is performed under an inert atmosphere.
9. A battery, characterized in that: The negative electrode active material of the battery comprises the graphite negative electrode material according to any one of claims 1 to 6.
10. The battery according to claim 9, characterized in that: The battery includes a lithium ion battery, a sodium ion battery, a potassium ion battery, a zinc ion battery or an aluminum ion battery.